2008
DOI: 10.1016/j.cplett.2007.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of ladder-type polymers: Polythiophene and polypyrrole

Abstract: This article presents an ab initio study of four polymers, polythiophene, polypyrrole, ladder-type polythiophene, and ladder-type polypyrrole. Upon an analysis of the variation of the band gap when comparing the unconstrained and the ladder-type polymers, a discrepancy was found between the thiophene and the pyrrole polymer families. For polythiophene, the ladder-type polymer has a larger gap than the unconstrained polymer whereas the opposite is found for the pyrrole polymers. The structural properties and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…More details about the electronic properties of that latter polymer can be found in a previous study. 23 The four other ladder-type polya͒ Electronic mail: michel.cote@umontreal.ca. mers considered are based on this atomic structure.…”
Section: First Principles Elaboration Of Low Band Gap Ladder-type Polmentioning
confidence: 99%
See 1 more Smart Citation
“…More details about the electronic properties of that latter polymer can be found in a previous study. 23 The four other ladder-type polya͒ Electronic mail: michel.cote@umontreal.ca. mers considered are based on this atomic structure.…”
Section: First Principles Elaboration Of Low Band Gap Ladder-type Polmentioning
confidence: 99%
“…A deeper study of the electronic properties of LPT and LPPy and their nonladder configurations using different basis sets and functionals has been reported in a previous article. 23 Considering first the LPT band structure, the minimum energy gap is found at ⌫ with a value of 1.58 eV. Note that this is a LDA value, and it is likely to strongly underestimate the real energy gap and does not take into account the excitonic effect.…”
Section: First Principles Elaboration Of Low Band Gap Ladder-type Polmentioning
confidence: 99%
“…[25] The synthesis of conducting polymers possessing enhanced stability is a very important goal, and polythiophenes [26] and polypyrroles [27] have often been investigated in this regard. [29] DFT calculations suggested that such polymers were characterized by a small distance between the valence band and the conduction band (i.e., band gap). Oyama and co-workers performed electropolymerization of 1 and some of its simple derivatives.…”
Section: Reactivitymentioning
confidence: 99%
“…They decided to follow theoretical investigations to prove that ladder-type compounds had less conformational freedom than that of polyenes. [29] DFT calculations suggested that such polymers were characterized by a small distance between the valence band and the conduction band (i.e., band gap). This phenomenon probably arises from the polymers planar structure, which causes more effective overlap of the p orbitals, and hence, more efficient conduction of charge along the polymer chain.…”
Section: Reactivitymentioning
confidence: 99%
“…The molecular quantum chemical calculations were performed essentially using the framework of the Kohn‐Shan Density Functional Theory (DFT)14 implemented in the Gaussian 03 program package 15. All calculations on the studied oligomer of this work were done on cluster machines in the CCIPL (Intensive Computing center at the University of Nantes (Pays de la loire)).…”
Section: Computational Detailsmentioning
confidence: 99%